Coordination of bank branches under uncertainty - Reinhart Schmidt (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1981)
Bank planning models should at least meet two requirements. Firstly, the multiperiod character of most banking activities should be considered. Secondly, one should allow for the uncertainty of future events. Lots of models have been constructed fulfilling these requirements. But only in a few models the problem of the underlying organizational structure of the bank has been incorporated. This must be criticized because the success of model implementation depends upon how the formal planning model is embedded in the organization ...
Keywords: 650